The Effects of Classroom Interaction on Studentsâ€™ Academic Achievement at Secondary School Level - Hussain, Liaqat; Jamil, Asif; Ameen, Iqbal; Bakhsh, Khuda (Mediterranean Journal of Social Sciences, 2011)
This research study focused on investigating â€œThe effects of classroom interaction on studentsâ€™ academic achievement atsecondary school levelâ€. The main objective of the study was to see the studentsâ€™ academic achievement with and without classroominteraction. The study was significant because it tells about the effects of classroom interaction at the secondary school level. The populationof the study was all the secondary level school students. 60 students studying in Class 9th of University WENSAM School and Collegewere taken as the sample of the study. The study was experimental, and pre-test, post-test were used for the collection of data. Theexperimental group was taught by the classroom interaction and the control group without classroom interaction method. Mean Standarddeviation, variance and the difference between means t-statistics were used for the analysis of data. The result showed that experimentalgroup performed significantly better than the control group on the post-test. It is recommended that teachers should adopt interactivelearning style in their classrooms because it actively engages students in the learning process. Teachers may be provided support so that theymay implement various interactive activities in the classrooms.